Effects of Powder from Passiflora Edulis Peel on Dough Properties and Bread Quality - Nguyen, Dang My Duyen; Pham, Thanh Huyen; Trieu, Minh Hau (Journal of Technical Education Science, 2022)
In this work, we aimed to experimentally investigate the influences of the addition of passion fruit powder on finished bread characteristics, i.e., the quality and sensory perception, and the dough physical-chemical properties. The substitution rate of the passion fruit peel powder ranged from 5 to 20% of the wheat flour by weight. In order to study the dough properties, various parameters such as the moisture content, gluten content, yeast gas production, and dough structure were evaluated. Additionally, the finished bread characteristics, e.g., the color, flavor, and nutritional content, were also assessed and analyzed. Results showed that the dough properties and bread structure were strongly dependent on the amount of passion fruit peel powder added. For instance, the volume of bread was observed to be dramatically reduced with the increasing substitution rate of the passion fruit peel powder. Moreover, the polyphenol contents in bread samples were 1355 mg/kg, 1637 mg/kg, 1773 mg/kg, and 1838 mg/kg for the substitution rate of 5%, 10%, 15%, and 20%, respectively. Amongst these, the bread with 10% passion fruit peel powder was the most preferred sample.